2018
DOI: 10.1038/s41598-018-24811-3
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive response of neonatal sepsis-derived Group B Streptococcus to bilirubin

Abstract: Hyperbilirubinemia is so common in newborns as to be termed physiological. The most common bacteria involved in early-onset neonatal sepsis are Streptococcus agalactiae, commonly called Group B Streptococcus (GBS). Whilst previous studies show bilirubin has antioxidant properties and is beneficial in endotoxic shock, little thought has been given to whether bilirubin might have antibacterial properties. In this study, we performed a transcriptomic and proteomic assessment of GBS cultured in the presence/absenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 27 publications
0
15
0
1
Order By: Relevance
“…Recently, it has been shown that neonatal hyperbilirubinemia may protect newborns from Streptococcus agalactiae associated sepsis, thereby suggesting an evolutionary role of hyperbilirubinemia …”
Section: Jaundice and Cholestatic Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been shown that neonatal hyperbilirubinemia may protect newborns from Streptococcus agalactiae associated sepsis, thereby suggesting an evolutionary role of hyperbilirubinemia …”
Section: Jaundice and Cholestatic Dysfunctionmentioning
confidence: 99%
“…agalactiae associated sepsis, thereby suggesting an evolutionary role of hyperbilirubinemia. (25) Heme degradation products Z-BOX A and B, which are elevated in cholestatic liver injury, show dose-dependent intrahepatic and extrahepatic cytotoxicity. (26) Collectively, impaired hepatobiliary transport and BA signaling contributes to cholestasis and may have widespread implications for control of metabolism, inflammation, gut integrity, and microbiota.…”
Section: Figmentioning
confidence: 99%
“…Analysis revealed that increasing levels of bilirubin negatively correlated with GBS growth [26]. Studies by Hijona et al seem to be optimistic.…”
Section: Discussionmentioning
confidence: 93%
“…The PPARα mediated effects account for at least partly the anti‐obesity and anti‐diabetic effects of bilirubin . Bilirubin is also anti‐bacterial, and this property was recently shown to provide natural protection against prenatal sepsis …”
Section: Bioactive Heme‐derived Bilins Relevant To Medicine and Agricmentioning
confidence: 88%
“…Also, being more hydrophilic than bilirubin IXα, the BVRB‐generated isomers are less capable of crossing the placental barrier contributing further to bilirubin accumulation (hyperbilirubinimea or jaundice) in the fetus and neonates ,. Such accumulation is speculated to have a protective role against streptococcal sepsis due to the antibacterial action of the bilirubins . Interestingly, BVRB is also expressed in hepatocellular carcinomas and prostate cancer cells…”
Section: Heme Oxygenase and Pathways Toward Bilinsmentioning
confidence: 99%